PEMAHAMAN EPISTIMOLOGI GURU TERHADAP INTERGRASI SAINS DAN AGAMA DI MTSN 1 SERANG - Elis Karwati Sri Mulyani; Mulyawan Safwandy Nugraha (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to explore the epistemological understanding of science and PAI teachers at MTsN 1 Serang in integrating science and religion. Using a qualitative approach of phenomenological design, data were collected through in-depth interviews, observations, and questionnaires. The results revealed that PAI teachers tend to use a deductive approach, with revelation as the main foundation in building learning, while science teachers adopt an inductive approach to connect scientific facts with religious values. Both approaches have advantages, but the integration of science and religion in madrasah still faces various challenges, especially related to curriculum support, limited facilities, and low training for teachers in the application of integrative methods. This research provides theoretical contributions in enriching the literature related to the integration of science and religion, as well as practical contributions in the form of recommendations for the development of integration-based education policies. The findings emphasise the importance of curriculum development that supports the integrative approach as well as the provision of adequate facilities and training. With these implications, the research is expected to contribute to the creation of a young generation that not only has broad scientific insights, but also a solid religious character, so as to be able to answer increasingly complex global challenges.